2014
DOI: 10.1523/jneurosci.0329-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cells Sense and Control Acetylcholine Spillover at the Neuromuscular Junction by α7 Nicotinic Receptors and Butyrylcholinesterase

Abstract: Terminal Schwann cells (TSCs) are key components of the mammalian neuromuscular junction (NMJ).How the TSCs sense the synaptic activity in physiological conditions remains unclear. We have taken advantage of the distinct localization of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) at the NMJ to bring out the function of different ACh receptors (AChRs). AChE is clustered by the collagen Q in the synaptic cleft and prevents the repetitive activation of muscle nicotinic AChRs. We found that BChE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 60 publications
1
48
0
Order By: Relevance
“…To complicate the scenario there is the recent discovery of BChE anchored by PRiMA on the surface of TSCs at mouse NMJs (Petrov et al, 2014). In conclusion, the cellular origin of the AChE released in the plasma in ALS and the consequences of its absence at the NMJ is still unclear, since many other functions, not related to the ACh hydrolysis, have been described (Soreq and Seidman, 2001).…”
Section: Cholinergic Dysfunction In Alsmentioning
confidence: 99%
“…To complicate the scenario there is the recent discovery of BChE anchored by PRiMA on the surface of TSCs at mouse NMJs (Petrov et al, 2014). In conclusion, the cellular origin of the AChE released in the plasma in ALS and the consequences of its absence at the NMJ is still unclear, since many other functions, not related to the ACh hydrolysis, have been described (Soreq and Seidman, 2001).…”
Section: Cholinergic Dysfunction In Alsmentioning
confidence: 99%
“…However, ACh released at mammalian NMJs can coactivate mAChRs to stimulate vasodilation in nearby blood vessels (WELSH AND SEGAL 1997), although the physiological significance of this stimulation is uncertain (HONG AND KIM 2017). ACh spillover has also been observed when quantal content is increased or when acetylcholinesterases are inhibited (STANCHEV AND SARGENT 2011;PETROV et al 2014). We have similarly observed that C. elegans ace-3 mutants with reduced acetylcholinesterase activity produce prolonged peristalses that are dependent on GAR-3.…”
Section: Ach Spillover May Produce Prolonged Peristalses In Eat-2 Mutmentioning
confidence: 77%
“…Another function of BChE is hydrolysis of the neurotransmitter acetylcholine. BChE acts as an independent and complementary modulator of acetylcholine levels at the mouse neuromuscular junction [27]. …”
Section: Discussionmentioning
confidence: 99%